(untitled) (Muitas Vozes, 2025)
This article aims to uncover the subjective and social meanings of black homosexual masculinities that emerge from the autobiographical narratives of three members of the Coletivo Afrobixas in Brasília/DF. These narratives were part of a Master’s research published in the book titled Title (2020). The study and interpretation of the corpus are guided by phenomenological approaches (MOREIRA, 2004; RIBEIRO JÚNIOR, 2003) and theoretical-methodological principles on life stories and (auto)biographical narratives (JOSSO, 2004; CHIZZOTTI, 2011). The theoretical framework addresses discussions on the representations of masculinities arising from the intersectional construction (CRENSHAW, 1989) between the identity categories of blackness (MUNANGA, 2009) and homosexuality (LINS; MACHADO; ESCOURA, 2016). In this context, we offer new interpretative perspectives on the subject to understand the (re)signification that the participant narrators imprint on their experiences, especially regarding their belonging to the Afrobixas Collective and their critical reflection on socially hegemonic models and values established within this group. The selected autobiographical narratives seem to broaden the phenomenological understanding of how black homosexuals construct their masculinities, linked to issues of race, class, and sexual orientation, highlighting their racial identity in the face of other emerging aspects in their life stories. KEYWORDS: Blackness. Homosexuality. Intersectionality. Black masculinity(ies). Autobiographical narratives.